Managers' Choices of Performance Measures in Promotion Decisions: An Analysis of Alternative Job Assignments - GRABNER, ISABELLA; MOERS, FRANK (Journal of Accounting Research, 2013)
ABSTRACT In this study, we investigate the choice of performance measures in promotion decisions. In particular, we examine the extent to which managers incorporate different performance measures for different types of job assignment. Based on a simple theoretical framework, we predict that, in making promotion decisions, the weight on current job performance decreases with increases in the change in tasks upon promotion, while the weight on subjective assessments of ability increases. This result basically follows from the premise that, with increased changes in tasks between hierarchical levels, the ability to master the current job says little about the ability needed in the next job, which makes current job performance less informative and increases the emphasis on subjective assessments. Using panel data of a retail bank, we find that individual managers behave according to our predictions. By examining the choice of performance measures in promotion decisions, we are able to provide unique insights into the incentive versus sorting roles of promotions, which has important implications for performance measurement and incentive system design.